Dampak Permainan Lego terhadap Perkembangan Kognitif Anak Usia Dini - Martini, Fepy; Rahmadyanti, Rahmadyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of Lego games on cognitive development of early childhood (5-6 years) in Ra Bani Asyyfa and Paud Nurul Hassanah Pandeglang Banten. The method used is quesi experiment with Non Equivalent Control Group Design approach. The sampling technique uses total sampling technique. The sampling technique uses total sampling technique. The research results showed that out of 30 games, the majority of children's cognitive balance started to be balanced (MB) when they were given a game of playing, namely 21 games (70%) were playing. Meanwhile, of the 30 respondents, the majority of children's cognitive balance was attributed to playing games, as many as 25 respondents (83%) were categorized as very well balanced (BSB), but there were 5 respondents (17%) whose cognitive development was still developing according to expectations (BSH). This was caused by many types of the respondent's gender is male based on, The results of the Wilcoxon Uiji are known as the Asymp value. Sig. (2-tailed) equal to 0.001 < 0.005. Conclusion There is a significant relationship between the influence of Lego games on the cognitive development of early childhood (5-6 years). Keywords: Playing Lego , Cognitive , Child Development, Ages 5-6